Charged Massive Particle’s Tunneling from Charged Nonrotating Microblack Hole - Soleimani, M.J.; Abbasvandi, N.; Radiman, S.; Wan Abdullah, W.A.T. (Hindawi Publishing Corporation, 2016)
In the tunneling framework of Hawking radiation, charged massive particle’s tunneling in charged nonrotating TeV-scale black hole is investigated. To this end, we consider natural cutoffs as a minimal length, a minimal momentum, and a maximal momentum through a generalized uncertainty principle. We focus on the role played by these natural cutoffs on the luminosity of charged nonrotating microblack hole by taking into account the full implications of energy and charge conservation as well as the backscattered radiation.